The decline of manufacturing employment and the rise of the far-right in Austria - Karim Bekhtiar (Johannes Kepler University of Linz, Department of Economics, 2023)
In recent decades right-wing populist parties have experienced increased electoral success in many western democracies. This rise of the far-right, which is strongly built on the support of the working class, coincides with a sharp decline of the manufacturing sector. This paper analyzes the contribution of this manufacturing decline to the rise of the Austrian far-right. Overall the decline in manufacturing employment has strongly contributed to this rightward shift in the political landscape, with the manufacturing decline explaining roughly 43% of the observed increase in far-right vote-shares between 1995 and 2017. This effect is entirely driven by increases in natives unemployment rates, which increased considerably due to the manufacturing decline. Regarding the influences of the forces underlying the manufacturing decline, namely international trade and automation technologies, suggests that both forces contributed in roughly equal parts to this development.
Keywords: D72; F14; J21; J23; O14; R23; 330; Manufacturing; Trade; Robots; Voting; Populism